Facing Death Anxiety: Effects of Professional Exposure To Death and Dying - Curtis, Kelly; Dagnall, Neil; Drinkwater, Kenneth; Denovan, Andrew (Journal of Scientific Exploration, 2023)
Previous research has examined the relationship between exposure to death and dying and death anxiety. However, the extent to which research in this area provides a coherent body of work is unclear. To investigate varied exposures of death and dying and to reproduce findings, a measure that encompasses the range of ways in which people can be exposed is necessary. Accordingly, this study developed a new measure, the Exposure to Death and Dying Scale (ED&DS), and investigated specifically how professional exposure to death and dying was related to death anxiety in high-exposure and non-exposure professions. Professional exposure is defined as exposure to death and dying in a professional setting, as opposed to in one’s personal relationships or with one’s self. The Death Anxiety Scale Extended (DAS-E) was used to provide a score for unease surrounding death. Participants (N = 468) were separated into different groups based on their profession: non-exposure professions and high-exposure professions, which consisted of 6 sub-categories: mental health professionals, the general medical field, nursing, mortuary professionals, end-of-life care, and forensic professionals. Professional exposure rates to both death and dying were calculated, as well as death anxiety scores and time spent in each profession. Non-exposure professions were shown to have lower levels of exposure than all categories of high-exposure professions. One-way ANOVA revealed that exposure (vs. non) professionals had a lower level of death anxiety. High-exposure occupations varied in levels of death anxiety. The mental health group had the highest mean death anxiety (111.52), followed by the forensic professionals (107.36), general medical field (106.66), nurses (104.79), mortuary professionals (104.60), and end-of-life carers (93.89). Although there was a trend toward a decline in death anxiety with increasing time spent in high-exposure occupations, there was also an increase in death anxiety among individuals with the longest tenure in their field, indicating that this is not a clear linear relationship. Overall, this study showed that the higher professional exposure to death and dying, the lower that individual’s reported death anxiety was, regardless of the type of exposure experienced.